DAMPAK PERBEDAAN POLA ASUH ORANG TUA TERHADAP KESADARAN GENDER ANAK(STUDI KASUS ORANG TUA REMAJA “D” YANG BERPERILAKU FEMINIM DI DESA MUARA PINANG KABUPATEN EMPAT LAWANG) - Gina Apri Lestari; Abddurrazaq; Neni Noviza (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This research is entitled The Impact of Different Parenting Patterns on Gender Awareness of Adolescents "D" Who Behave Feminically in Muara Pinang village, Empat Lawang Regency. This study aims to explain the parenting style used by the parents of male adolescents "D" and to determine the effect of various parenting philosophies on gender awareness of male adolescents "D." Case study research methods and forms of field research are both used in this study, which takes a qualitative approach. The parents of adolescent "D" were used as research subjects and primary data sources, while adolescents "D" were used as secondary research data sources. using observation, interviews, and documentation as data collection methods. In this study, time series analysis, data explanation, and pattern matching were used as data analysis methodologies. The findings of this study indicate that the permissive parenting style used by parents of adolescents "D" is a parenting style that allows their children to do whatever they want, while the influence of other parenting styles used by parents of adolescents "D" is that children show the same behavior. Children also exhibit deviant behavior, such as liking the same sex, and are considered feminine if they behave like women in terms of cooking, housekeeping, grooming, and wearing accessories.